Male Infertility: An Epidemiological and Clinical Profile at the Andrology Unit of Dr. Soetomo Hospital, Surabaya, Indonesia - Antonius Wahyudi (Journal of Global Pharma Technology, 2020)
Objective: To discover and to lay out epidemiological features and clinical characteristics of patients with infertility problems who seek treatment at the Andrology Unit of Dr. Soetomo Hospital. Methods: A cross sectional study was conducted to men with infertility who sought treatment in the Andrology Unit of Dr. Soetomo Hospital ranging from January to December 2017. Only patients who lived together with their spouses were included as research subjects. Results: The average age of the patients was 33.76 years (age ranged from 25 to 46 years) and the average age of their spouses was 30.4 years (age ranged from 19 to 42 years). The average duration of infertility is 4.25 years (between 1 year and 13 years). Average age of puberty was 14.5 years old. First consultations were late with average of 4.46 years. From overall infertile patients, 90% of them were categorized as primary infertility. History of smoking was found in 84 people (68.29%), history of wearing tight pants 27 people (21.95%). In terms of Body Mass Index(BMI), we found that underweighted patients comprise 7% (9 patients) from total liable subjects, while 55 people (55%) were in the area of ideal body mass, 46 people were overweight (35%), whereas obesity was found in 13 subjects (10%). The results of semen analysis showed that the most case were asthenoteratozoospermia 34 people (27.6%). A careful history, physical examination and semen analysis can determine the cause of male infertility. The cause of male infertility in Surabaya, Indonesia is very complex, which involves older age, delayed consultation and background as risk factors that cause abnormalities in semen analysis. Keywords: Male infertility, epidemiology, andrology, Dr. Soetomo Hospital, Surabaya, Indonesia.